Effect of The Sweet Potato Against Mice on Blood Glucose of Diabetes Mellitus - Ai Kustiani; Wilda Raziq (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2018)
The aim of this study was to analyze the effects of the sweet potato to the levels of blood glucose on diabetic mellitus mice. This study had been carried out with a sample of 25 mice which were divided into 5 groups. The levels of blood glucose on mice before treating with rice flour and sweet potato flour on the negative control group (KN) was 76.2 ± SD, on the positive control group (KP) was 159.4 ± SD, on the 1st treatment group (P1) was 159.4 ± SD, on the 2nd treatment group (P2) was 166.6 ± SD and 3rd treatment group (P3) was 161.2 ± SD. The average blood glucose levels on the 2nd treatment group (P2) before treatment was 166.6 ± SD and after treatment was 109.0 ± SD. The result showed a significant difference based on the statistical data (p 0.05) between 4 test groups of mice. There was a big difference on the average blood glucose levels before and after treatment o P2 and P3. It is concluded that the treatment of sweet potatoes gives a positive effects on the blood glucose levels of diabetic mellitus mice.